2020
DOI: 10.1093/eurpub/ckaa165.453
|View full text |Cite
|
Sign up to set email alerts
|

Poor oral health and incidence of disability: results from studies of older people in the UK and USA

Abstract: Background To examine the association between oral health markers and disability 4 years later in two population-based studies of older people in the UK and USA. Methods Analyses were conducted in the British Regional Heart Study (BRHS) comprising older men (n = 2147) and the Health, Aging and Body Composition (HABC) Study comprising American older men and women (n = 3075). Data from a 4-year follow up period were used. Oral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Our findings could deepen the understanding of the role social and psychological factors played in the relationship between oral health and functional limitations and provide a reference for specific interventions to counter functional limitations. This study found that tooth loss had a significant positive association with functional limitations, consistent with Hypothesis 1 and previous studies that found significant associations between tooth loss and greater odds of mobility limitations or function impairment in older Notes: β, standardized coefficients; SE, the standard error of indirect effects estimated; LLCI, lower limit confidence interval; ULCI, upper limit confidence interval; IADL, instrumental activities of daily living; SWB, subjective well-being adults [4][5][6]19]. This related mechanism can be considered from the causes of tooth loss.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our findings could deepen the understanding of the role social and psychological factors played in the relationship between oral health and functional limitations and provide a reference for specific interventions to counter functional limitations. This study found that tooth loss had a significant positive association with functional limitations, consistent with Hypothesis 1 and previous studies that found significant associations between tooth loss and greater odds of mobility limitations or function impairment in older Notes: β, standardized coefficients; SE, the standard error of indirect effects estimated; LLCI, lower limit confidence interval; ULCI, upper limit confidence interval; IADL, instrumental activities of daily living; SWB, subjective well-being adults [4][5][6]19]. This related mechanism can be considered from the causes of tooth loss.…”
Section: Discussionsupporting
confidence: 88%
“…Many studies have confirmed that oral health is closely related to the risk of developing functional limitations [4]. Tooth loss, a key indicator of oral health, is no exception [5]. Studies have shown that tooth loss was linked to problems with instrumental activities of daily living (IADL), activities of daily living (ADL), and mobility [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation